What are the distributional implications of climate policies? Recent evidence from developing countries - Daniele Malerba (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
To avoid catastrophic effects on natural and human systems, bold action needs to be taken rapidly to mitigate climate change. Despite this urgency, the currently implemented and planned climate mitigation policies are not sufficient to meet the global targets set in Paris in 2015. One reason for their current inadequate rollout is their perceived negative distributional effects: by increasing the price of goods, climate mitigation policies may increase both poverty and inequality. In addition, they may disrupt labour markets and increase unemployment, especially in sectors and areas dependent on fossil fuels. As a result, public protests in many countries have so far blocked or delayed the implementation of climate policies. New avenues of research, discussed in this Briefing Paper, are turning the tide. First, it has been shown that carbon pricing may not be regressive in developing countries, contrary to the evidence in advanced economies. In a similar positive direction, findings from global-level and cross-country studies assessing the effects of climate mitigation policies on labour markets estimate that reaching climate goals will actually generate a small net increase in jobs. Nonetheless, the price effect of carbon pricing and the impact on the labour market of climate policies will both create losers: increases in prices would worsen poverty as lower-income households would need to pay more to purchase the same goods; similarly, specific countries, sectors, areas and workers (such as low-skilled ones) will witness job disruption or loss. Second, social protection policies can be implemented to compensate households and workers negatively affected by climate policies and to address negative distributional effects. Compensation for higher prices can be achieved through the use of cash transfers to households, which can be funded by revenues from climate policies such as carbon taxes. Full compensation can be achieved by using only a small share (about 30%-50% according to case studies) of the tax revenues generated. The remaining share could be used for other purposes, such as climate-friendly investments. Similarly, when looking at labour market effects, social protection, especially labour market policies such as retraining and unemployment relief, become critical in addressing the needs of negatively affected workers. Clearly, the achievement of environmental and social goals need not be mutually exclusive. With appropriate policy mixes, both poverty and environmental degradation can be reduced. This policy implication needs to be communicated more widely to increase the acceptance of climate polices. This is partially already achieved by recent plans such as the European Green Deal. From a research and policy perspective, more studies in developing countries are needed, including evidence on non-market climate policies and extending beyond the short-term effect of higher prices on the purchasing power of households. Finally, international cooperation can play an important role in policy coordination, financing and building social protection systems in lower-income countries.
Keywords: 330